Acute and chronic effects by nicotine on striatal neurotransmission and synaptic plasticity in the female rat brain - Lucente, Erika; Söderpalm, Bo; Ericson, Mia; Adermark, Louise (Frontiers in Molecular Neuroscience, 2023)
Introduction Tobacco use is in part a gendered activity, yet neurobiological studies outlining the effect by nicotine on the female brain are scarce. The aim of this study was to outline acute and sub-chronic effects by nicotine on the female rat brain, with special emphasis on neurotransmission and synaptic plasticity in the dorsolateral striatum (DLS), a key brain region with respect to the formation of habits. Methods In vivo microdialysis and ex vivo electrophysiology were performed in nicotine naïve female Wistar rats, and following sub-chronic nicotine exposure (0.36 mg/kg free base, 15 injections). Locomotor behavior was assessed at the first and last drug-exposure. Results Acute exposure to nicotine ex vivo depresses excitatory neurotransmission by reducing the probability of transmitter release. Bath applied nicotine furthermore facilitated long-term synaptic depression induced by high frequency stimulation (HFS-LTD). The cannabinoid 1 receptor (CB1R) agonist WIN55,212-2 produced a robust synaptic depression of evoked potentials, and HFS-LTD was blocked by the CB1R antagonist AM251, suggesting that HFS-LTD in the female rat DLS is endocannabinoid mediated. Sub-chronic exposure to nicotine in vivo produced behavioral sensitization and electrophysiological recordings performed after 2-8 days abstinence revealed a sustained depression of evoked population spike amplitudes in the DLS, with no concomitant change in paired pulse ratio. Rats receiving sub-chronic nicotine exposure further demonstrated an increased neurophysiological responsiveness to nicotine with respect to both dopaminergic- and glutamatergic signaling. However, a tolerance towards the plasticity facilitating property of bath applied nicotine was developed during sub-chronic nicotine exposure in vivo. In addition, the dopamine D2 receptor agonist quinpirole selectively facilitate HFS-LTD in slices from nicotine naïve rats, suggesting that the tolerance may be associated with changes in dopaminergic signaling. Conclusion Nicotine produces acute and sustained effects on striatal neurotransmission and synaptic plasticity in the female rat brain, which may contribute to the establishment of persistent nicotine taking habits.